Los mercados de abastos en la legislación peruana: el caso del Área Metropolitana de Lima en el contexto de emergencia sanitaria por el COVID-19 - Devoto Ykeho, Andres (2023)
The article develops the regulation of the food market service in Peruvian legislation, after the new regulatory changes that occurred before and during the COVID-19 pandemic. In addition, the existing typologies on markets, the public actors involved and the administrative legal regime that adheres to the Peruvian legal system are studied. Finally, two aspects that food markets maintain in regard to the new legislation related to urban development and food safety are analyzed. Likewise, after a legal analysis of the regulations, administrative doctrine, and jurisprudence we found an underway process to recover the role that the public administration has in the promotion, construction and operation of the food markets, after the processes of liberalization and privatization that occurred in Peru during the nineties.